Position regulation in Cartesian space of a class of inextensible soft continuum manipulators with pneumatic actuation - Franco,E; Garriga,Casanovas A; Tang,J; Rodriguez,y Baena F; Astolfi,A (Mechatronics, 2021)
This work investigates the position regulation in Cartesian space of a class of inextensible soft continuum manipulators with pneumatic actuation subject to model uncertainties and to unknown external disturbances that act on the tip. Soft continuum manipulators are characterised by high structural compliance which results in a large number of degrees-of-freedom, only a subset of which can be actuated independently or instrumented with sensors. External disturbances, which are common in many applications, result in uncertain dynamics and in uncertain kinematics thus making the control problem particularly challenging. We have investigated the use of integral action to model the uncertain kinematics of the manipulators, and we have designed a new control law to achieve position regulation in Cartesian space by employing a port-Hamiltonian formulation and a passivity-based approach. In addition, we have compared two adaptive laws that compensate the effects of the external disturbances on the system dynamics. Local stability conditions are discussed with a Lyapunov approach and are related to the controller parameters. The performance of the controller is demonstrated by means of simulations and experiments with two different prototypes.